Strapping Rope Skills Training for Housewives to Utilize Free Time In Tualang Village, Siak District - Agnesiyah Sumbari Aldestu; Jamaris Jamaris (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2023)
This research is inspired with the aid of housewives who take benefit in their free time by means of processing strong waste into multipurpose items. The aim is to improve the abilities of housewives through training sports so we can boom know-how, increase circle of relatives earnings and enhance the welfare of the Tualang Village network. The purpose of this have a look at is to explain the education of woven strapping talents in phrases of the process, blessings, as well as supporting and inhibiting elements in accomplishing education. This research is a research the use of a qualitative method, with the studies method is a case study. The records assets in this examine had been housewives in Tualang Village who were members of the Tunas Harapan IKM as research subjects and the top of the Tunas Harapan IKM as studies informants. information series strategies used on this observe are observation, interviews and documentation. The information analysis approach used is data reduction, facts presentation and drawing conclusions. The information validity method is by using the usage of source triangulation. The effects showed that the capabilities schooling manner began from planning, implementation, mentoring, evaluation, and follow-up, the benefits of education in terms of information, independence and cooperation, helping factors, namely fine responses from contributors, lively participation chairperson, availability of substances and support from family and friends who assist every other. while the inhibiting thing is the cloth received is less. Keywords: Training, Strapping Webbing Skills for Housewives